Evolving Traditions: The Contemporary Dynamics of Uang Panai' in Bugis-Makassar Wedding Ceremonies - Masthurah, Nur; Amin, Fatimah Hidayahni; Sunusi, Seny Luhriyani; Hanafie, Nurharsya Khaer; Mohamad, Andi Riswan (Tamaddun Life, 2024)
The tradition of "uang panai'", a traditional dowry in Bugis-Makassar wedding ceremonies, plays a crucial role in preserving cultural heritage while adapting to contemporary societal changes. This study adopts a qualitative ethnographic approach to explore the evolving criteria for determining the price of uang panai' and its implications on social dynamics within the Bugis-Makassar community. Data were collected through observations and interviews with informants from various districts, supplemented by literature studies. The findings reveal that while lineage remains a predominant criterion, factors such as wealth, education, and occupation have gained significant importance. Wealthy and noble families often demand higher uang panai' to maintain their social status and ensure compatible marital matches. Education and occupation also significantly influence the dowry's value, reflecting the community's increasing emphasis on social mobility and economic stability. This study's novelty lies in its detailed examination of the interplay between traditional practices and modern socioeconomic factors, providing a comprehensive understanding of uang panai's' evolving role. The research highlights the dual function of uang panai' as a symbol of respect and a potential source of economic pressure, offering insights for balancing cultural preservation with economic realities. These findings contribute to the broader discourse on cultural adaptation and suggest avenues for future research on mitigating financial burdens associated with traditional practices. By elucidating the contemporary dynamics of uang panai', this study enhances our understanding of cultural practices and their adaptation in a rapidly changing society.